2018
DOI: 10.1016/j.ijbiomac.2018.05.027
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring glycogen biosynthesis through Monte Carlo simulation

Abstract: Glycogen, a complex branched polymer of glucose (average chain length ~10 monomer units), is the blood-sugar reservoir in humans and other animals. Certain aspects of its molecular structure relevant to its biological functions are currently unamenable to experimental exploration. Knowledge of these is needed to develop future models for quantitative data-fitting to obtain mechanistic understanding of the biosynthetic processes that give rise to glycogen structure. Monte Carlo simulations of the biosynthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The experimental results of R z and α-amylolysis indicated that the highest molecular density of GnG is found to be near the center of the particle. This result is in accordance with a Monte Carlo simulation of the 3D conformation of a glycogen β-particle, suggesting that the core of glycogen particles has a higher density than the periphery . The formation of a dense center is possible because there are no regulatory enzymes (such as glycogen debranching enzymes) included in the enzyme system of the SP-GP-BE method.…”
Section: Resultssupporting
confidence: 86%
“…The experimental results of R z and α-amylolysis indicated that the highest molecular density of GnG is found to be near the center of the particle. This result is in accordance with a Monte Carlo simulation of the 3D conformation of a glycogen β-particle, suggesting that the core of glycogen particles has a higher density than the periphery . The formation of a dense center is possible because there are no regulatory enzymes (such as glycogen debranching enzymes) included in the enzyme system of the SP-GP-BE method.…”
Section: Resultssupporting
confidence: 86%
“…glycogen, which is similar to starch in many ways (Zhang et al, 2018)), and so no model can be used for the desired separation. For these reasons, we have simply divided the w(logRh)…”
Section: Resultsmentioning
confidence: 99%
“… Besford et al (2015) used small angle X-ray scattering (SAXS) to analyze mouse β-particles, revealing these particles to be randomly branched polymers rather than hierarchical or fractal polymers. In addition, Zhang et al (2018) also used Monte Carlo model to simulate glycogen β particle formation, which also generated randomly branched polymers.…”
Section: Glycogen β Articlesmentioning
confidence: 99%
“…The technique, involving the scattering of X-rays from all electrons in a sample, allows identification of the pair-distance distribution (i.e., the distribution of all distances between electrons in a single average particle). In addition, Zhang et al (2018) uses the Monte Carlo model to simulate glycogen structure. The result shows that the radial density reaches maximum close to the center of glycogen particles, which is consistent with random growth pattern of glycogen particles ( Zhang et al, 2018 ).…”
Section: Glycogen β Articlesmentioning
confidence: 99%
See 1 more Smart Citation